Physical Modifications of Starch (Springer Singapore, 2018)
This book provides comprehensive information on starch modification using physical approaches - a field that has attracted increasing interest in recent years due to the fact that it is no longer desirable to label starch a modified. The required functionalities can be conveniently achieved by physical methods that are less expensive and more environmentally friendly. Intended for researchers and product developers working on starch, the book summarizes recent developments in the areas of starch physical modifications and reviews the structure, function and potential industrial applications of modified starch. Dr. Zhongquan Sui is an Associate Professor at Shanghai Jiao Tong University. Dr. Xiangli Kong is an Assistant Professor at Zhejiang University.